Retention and diffusion of radioactive and toxic species on cementitious systems: Main outcome of the CEBAMA project. (January 2020) - Grambow, B.; López-García, M.; Olmeda, J.; Grivé, M.; Marty, N.C.M.; Grangeon, S.; Claret, F.; Lange, S.; Deissmann, G.; Klinkenberg, M.; Bosbach, D.; Bucur, C.; et al.
Abstract: Cement-based materials are key components in radioactive waste repository barrier systems. To improve the available knowledge base, the European CEBAMA (Cement-based materials) project aimed to provide insight on general processes and phenomena that can be easily transferred to different applications. A bottom up approach was used to study radionuclide retention by cementitious materials, encompassing both individual cement mineral phases and hardened cement pastes. Solubility experiments were conducted with Be, Mo and Se under high pH conditions to provide realistic solubility limits and radionuclide speciation schemes as a prerequisite for meaningful adsorption studies. A number of retention mechanisms were addressed including adsorption, solid solution formation and precipitation of radionuclides within new solid phases formed during cement hydration and evolution. Sorption/desorption experiments were carried out on several anionic radionuclides and/or toxic elements which have received less attention to date, namely: Be, Mo, Tc, I, Se, Cl, Ra and 14 C. Solid solution formation between radionuclides in a range of oxidation states (Se, I and Mo) with the main aqueous components (OH −, SO4 −2, Cl − ) of cementitious systems on AFm phases were also investigated. Highlights: Understanding anion retention in cementitious materials. Reducing uncertainties with respect to radionuclide behaviour in hardened cement pastes. Justifying assumptions used when representing radionuclide migration in safety assessments. Improving databases for assessing adsorption of radionuclides in fresh and degraded cement systems.